Age-dependent effects of acute methylphenidate on amygdala reactivity in stimulant treatment-naive patients with Attention Deficit/Hyperactivity Disorder. (30th November 2017) - Bottelier, Marco A.; Schrantee, Anouk; Ferguson, Bart; Tamminga, Hyke G.H.; Bouziane, Cheima; Kooij, J.J. Sandra; de Ruiter, Michiel B.; Reneman, Liesbeth
Abstract: In the present study, we investigate whether methylphenidate (MPH) affects emotional processing and whether this effect is modulated by age. We measured amygdala reactivity with functional Magnetic Resonance Imaging (fMRI) during processing of angry and fearful facial expressions in male stimulant treatment-naive patients with ADHD (N = 35 boys; N = 46 men) and 23 healthy control subjects (N = 11 boys; N = 12 men). In ADHD patients, we also measured amygdala reactivity 90 min after an acute oral challenge with MPH (0.5 mg/kg). Mean amygdala reactivity was analyzed for all subjects using a repeated measures analysis of variance (ANOVA). Whole-brain maps were analyzed for the patients only. At baseline, we found a age*diagnosis effect approaching significance (p = 0.05) in the right amygdala due to lower reactivity in children with Attention Deficit/Hyperactivity Disorder (ADHD) vs. controls (−31%), but higher reactivity in adults with ADHD vs. controls (+31%). MPH significantly reduced right amygdala reactivity in all patients, resulting in further reductions in children. In the left amygdala, reduction of amygdala reactivity was confined to adult ADHD patients whereas there was no change in children with ADHD. MPH-induced decrease of amygdala reactivity in adults might be a promising avenue for managing emotional dysregulation when replicated for chronic MPH treatment. Highlights: Emotion dysregulation is a key feature of ADHD and causes serious impairment. Evidence is emerging that dopamine modulation of the amygdala reactivity plays an important role in in the pathophysiology and treatment of emotion regulation problems in ADHD. Using fMRI to assess amygdala reactivity, we here report that adults with ADHD show higher amygdala reactivity than children with ADHD. We measured amygdala reactivity with functional Magnetic Resonance Imaging (fMRI) during processing of angry and fearful facial expressions before and 90 minutes after an acute oral challenge with MPH (0.5mg/kg) in male stimulant treatment-naive patients with ADHD (N = 35 boys; N = 46 men) and 23 healthy control subjects (N = 11 boys; N = 12 men). Mean amygdala reactivity was analyzed for all subjects using a repeated measures analysis of variance (ANOVA). Whole-brain maps were analyzed for the patients only. In addition, methylphenidate, the prime treatment for ADHD, can reduce the heightened amygdala reactivity in adults. We measured amygdala reactivity with functional Magnetic Resonance Imaging (fMRI) during processing of angry and fearful facial expressions before and 90 min after an acute oral challenge with MPH (0.5 mg/kg) in male stimulant treatment-naive patients with ADHD (N = 35 boys; N = 46 men) and 23 healthy control subjects (N = 11 boys; N = 12 men). In the left amygdala, reduction of amygdala reactivity was confined to adult ADHD patients (-36.3%, F1, 45 = 6.71; p = 0.01) whereas there was no change in children with ADHD (F1, 38 = 0.33; p = 0.57). These data are the first to demonstrate that emotion regulation is modulated in an age-dependent manner. As emotional problems are prevalent among ADHD patients and influence the course and outcome of ADHD, these findings bear potential clinical relevance.